The Analysis of the Transformation of Forest Landscapes in the Eastern Zangezur Region of Azerbaijan Based on Satellite Imagery - Faig Abdurahmanov (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2023)
Forested areas, which are considered as the most valuable national natural assets of Azerbaijan, encompass the interconnectedness of soil, water, trees, shrubs, herbaceous plants, wildlife, and microorganisms in their biological development. For this reason, the protection and research of the forests are considered one of the important studies. In this article, we have studied the forests of the Eastern Zangezur region where formed based on the decree of the President of the Republic of Azerbaijan, Ilham Aliyev, on July 7, 2021, which united the districts of Kalbajar, Lachin, Gubadli, Zengilan, and Jabrayil. The Eastern Zangezur region has a rich forest area which approximately a quarter of the region is covered with forests.  However, unfortunately, the forest areas within the district have been strongly degraded and destroyed over the past 30 occupation years. The main causes of this destruction are attributed to illegal logging, deliberate forest fires, wars and other factors.